Lung Middle Lobe Laceration Needing Lobectomy as Complication of Nuss Bar Removal - Brice Henry; Valérie Lacroix; Thierry Pirotte; Pierre-Louis Docquier (Case Reports in Orthopedics)
Minimally invasive procedure for the treatment of pectus excavatum as described by Nuss has been used from 1987. The bar initially introduced blindly is now introduced under thoracoscopic control to increase safety of the procedure. It is usually removed two to three years after its insertion in a one-day procedure. Complications of the bar removal are rare but potentially serious. We report the case of a serious complication which occurred immediately after the Nuss bar removal. A 15-year-old boy underwent a Nuss procedure for a severe pectus excavatum without relevant complication. The bar has been removed two years after its insertion in a minimally invasive procedure. Unfortunately, he developed in the immediate postoperative period a hemopneumothorax due to a right middle lobe laceration which required a middle lobectomy by thoracotomy for hemostasis. Lesions of intrathoracic organs are a rare but potentially serious complication of the removal of the Nuss bar. We now propose to perform this procedure under thoracoscopic control to avoid it. In our experience, adhesions between the bar and the pleura are always present, and those with potential risk for bleeding or inducing intrathoracic organ lesions are suppressed prior to the bar removal.